Standardisation of Shade Requirement in Dendrobium - Sheron Fernandez (Department of Pomology and Floriculture, College of Horticulture, 2001)
An experiment was carried out in the Department of Pomology and Floriculture, College of Horticulture, Kerala Agricultural University, Thrissur, during 2000-2001, to standardize the shade requirement for Dendrobium variety Sonia Born J 0 and Renappa. The effect of different levels of shade on the morphological characters, flower production and quality of flowers were assessed. Results revealed that the different levels of shade significantly influenced the morphological characters of the plant, viz., plant height, shoot production, internodal length, leaf production and leaf area. Maximum plant height was obtained for fifty per cent double level shading. With respect to shoot production, 25 and 35 per cent double levels of shade performed better. The length of the internode was maximum for 50 per cent double level shading. Highest leaf production was noticed in 35 per cent double level shading which was statistically on par with 50 per cent double level of shade. Flower quality and flower production were markedly influenced by shade. Earliness in flowering was observed for those treatments receiving more light condition. Twenty five per cent single level shading was the earliest to flower in the group, while the longevity of the spike on the plant was more in 50 per cent single and double levels of shade. Vase life was significantly high in 25 per cent (15.50 days) and 50 per cent (14.88 days) double levels of shade. Longest spike was obtained in 50 per cent single level shading, while the length of the rachis was maximum in 50 per cent double level shading. Fifty per cent single level shading was distinctly superior to all other treatments with respect to the number of flowers per spike. Maximum spike production was noticed in 25 per cent double level shading. Anthocyanin content in flowers was found maximum under 50 per cent double level shading.